Levels of awareness of procedural sedation and analgesia among non-anaesthesiologists - Ben-Israel, Karin-Ann (My University, 2015)
Procedural sedation and analgesia (PSA) is performed by a variety of non-anaesthesiologists in numerous hospital settings. PSA guidelines have been formulated by a number of organisations in order to standardise practice and improve patient safety. Despite this it was uncertain whether PSA practitioners were aware of and used these guidelines, and whether the recommended equipment and drugs required for the safe delivery of PSA are available. The purpose of this research was to assess the demographic profile of non-anaesthesiologist PSA providers at Chris Hani Baragwanath Academic Hospital (CHBAH), their awareness of the South African Society of Anaesthesiologists (SASA) Sedation Guidelines 2010 and their level of comfort when performing PSA. An audit of available equipment and drugs in PSA settings outside the operating theatre was also done. The study revealed a gap in guideline knowledge, with respondents scoring a mean of 63.06%. The study also revealed that junior doctors performed better than consultants (p=0.008), but were more likely to feel uncomfortable administering PSA (0.031). A significant relationship between pharmacology knowledge and levels of comfort was also revealed, with those scoring higher in this section being more comfortable identifying and managing complications related to PSA (p=0.014). The equipment and drug audit identified many deficiencies in some of the locations assessed. These locations will require major improvements in order to increase patient safety. The audit also identified locations that are well equipped that only require minor improvements. PSA offers an alternative to general anaesthesia in a theatre environment; however, in order to ensure patient safety, practitioners need to adhere to recommended practice guidelines and the required equipment and drugs need to be readily available.
Keywords: Anesthesia